The importance of PLA in secondary schools - Horváth Orsolya (2006)
In this thesis I focused on the importance of Prior Learning Assessment. I met this through adult training and I thought I could use it in secondary schools also. I did an experiment where I tried to prove that it helps the students to acquire more. After the experiment I suggest every teacher to try this. It needs more work, but I believe it deserves.